Geneza koncepcji zrównoważonego rozwoju oraz proces jej kształtowania się poprzez zawieranie globalnych porozumień - Rydz-Żbikowska, Anna (Gospodarka w Praktyce i Teorii, 2012)
The aim of this article is a characterization of the process of the shaping of the concept of sustainable development as well as a look at the influence that this concept has exerted on contemporary international politics, especially taking into account agreements of worldwide scope. This article is also an attempt to prove that the foundations of the concept of sustainable development can be traced to certain economic theories. The final chapter of this article is devoted to the presentation of individual conferences initiated by the United Nations in order to promote enduring and sustainable development on a world scale.